2017
DOI: 10.1155/2017/8249532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvesting Stage on Sweet Sorghum (Sorghum bicolor L.) Genotypes in Western Kenya

Abstract: Harvesting stage of sweet sorghum (Sorghum bicolor L. Moench) cane is an important aspect in the content of sugar for production of industrial alcohol. Four sweet sorghum genotypes were evaluated for harvesting stage in a randomized complete block design. In order to determine sorghum harvest growth stage for bioethanol production, sorghum canes were harvested at intervals of seven days after anthesis. The genotypes were evaluated at different stages of development for maximum production of bioethanol from flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(24 reference statements)
2
6
1
8
Order By: Relevance
“…Results for TPW, SW, and DPW reported here are similar to values from other sweet sorghum varieties for bioethanol production (from 35 to 52.12 t•ha −1 ) [44]. (Mn-4508 ); for JV, from 13,546.6 (EUSS10) to 22,976.9 L•ha −1 (SS04); and for • B, from 11.26% (Mn-1054) to 19.12% (SS-301) [41,45]. These parameters vary by genetic, climatic, and edaphic factors [46].…”
Section: Agronomic Parameterssupporting
confidence: 84%
See 1 more Smart Citation
“…Results for TPW, SW, and DPW reported here are similar to values from other sweet sorghum varieties for bioethanol production (from 35 to 52.12 t•ha −1 ) [44]. (Mn-4508 ); for JV, from 13,546.6 (EUSS10) to 22,976.9 L•ha −1 (SS04); and for • B, from 11.26% (Mn-1054) to 19.12% (SS-301) [41,45]. These parameters vary by genetic, climatic, and edaphic factors [46].…”
Section: Agronomic Parameterssupporting
confidence: 84%
“…Regarding In general, PH values obtained were higher than those reported by Oyier et al [41] for the EUSS10 genotype (1.88 m). There is great heterogeneity in plant size from different genotypes and varieties of sweet sorghum.…”
Section: Agronomic Parameterscontrasting
confidence: 65%
“…Hal ini disebabkan karena pada umur 101 HST kadar brix sudah mencapai tingkat maksimum pada semua perlakuan inilah saat terjadinya kadar brix maksimum. Sejalan dengan hasil penelitian Oyier et al (2017), yang menunjukkan bahwa pada umur tanaman 101-117 HST dapat menghasilkan nilai kadar brix yang tinggi. Selanjutnya pemberian pupuk silikat dan pupuk kandang berpengaruh nyata terhadap kadar brix pada umur 77 HST, 91 HST, 107 HST, dan 128 HST.…”
Section: Kadar Brix (Kadar Gula) Pada Batang Sorgumunclassified
“…Menurut Yukamgo dan Yuwono (2014), Pemberian pupuk silikat yang cukup pada tanaman serealia mampu memperoleh hasil yang baik, karena penambahan pupuk silikat dapat meningkatkan kekuatan dan ketahanan sel. Hasil produksi akan menurun jika kadar brix pada tanaman sorgum menghasilkan nilai yang tinggi, peningkatan kadar brix yang terdapat pada sorgum menunjukkan bahwa ketika biji mulai matang karna terdapat lebih banyak karbohidrat yang tersimpan di batang tanaman sorgum (Oyier et al, 2017) Pupuk kandang dapat menambah ketersediaan unsur hara dalam tanah yang dapat diserap oleh tanaman (Sutejdo, 2007). Bahan organik tersebut akan mempengaruhi dan memperbaiki sifat fisik tanah seperti, meningkatkan kemampuan memegang air, aerasi, resistensi terhadap erosi air, penetrasi akar dan menstabilkan suhu tanah, memperbaiki sifat kimia tanah seperti, meningkatkan ketersediaan mineral, stabilitas pH, nutrient reservoir, dan meningkatkan sifat biologi tanah, seperti merangsang aktifitas mikrobia yang berguna, mereduksi parasit (Soepardi, 1979).…”
Section: Kadar Brix (Kadar Gula) Pada Batang Sorgumunclassified
“…However, stage of maximum sugar accumulation varies in different varieties with some genotypes mainly accumulating sugars between dough stage and physiological maturity, whereas others accumulate sugars up to 15 days post-physiological maturity [60]. Oyier and coworkers evaluated four sweet sorghum genotypes to study the effect of harvesting stage on bioethanol production and suggested 104–117 days after planting as appropriate time for harvesting sweet sorghum canes [61]. …”
Section: Life Cycle and Growth Conditionsmentioning
confidence: 99%